(untitled) (Research, Society and Development, 2022)
Measles can be defined as a contagious disease of person-to-person dissemination through nasopharyngeal particles disseminated in the air and is one of the main causes of hospitalization of children, being directly linked to the nutritional status, immune status and socioeconomic situation of the patient. The objective of this research was to understand and analyze the role of nurses in the Brazilian National Health System in the control and prevention of measles. The search was done in the following libraries: Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL), and Google Scholar, using the Health Science Descriptors (DeCS), "Nursing" and "Measles", and the reported results were tabulated and analyzed. Three categories related to the importance of nursing in measles prevention were identified: its role as a health educator, providing guidance on vaccination, its importance in ensuring good vaccination coverage, and the need for training and continuing education. The importance of training nursing professionals to perform evidence-based practices and to carry out health education with mastery can be evidenced, thus reducing the number of infections in society caused by measles.